THE MAIN SYMPTOMS OF STRESS PRE-COMPETITIVE JUVENILE RUFFONI JUDO TEAM (Fiep Bulletin - online, 2011)
Today we live in a time that by the agitation of modern life and new lifestyle, everything happens so quickly we are all exposed to an overload of stimuli. It is known that stress in one form or another affects us all. The great growth and appreciation of the sports world in recent decades have provided an increase in appearance of training teams of children in several sports. The sport - especially the competitive - is synonymous of benchmark situations. Lima (1999) affirms that stress is an inherent aspect of the competition. Stefanello (2007) points that for some athletes; the sports competition can represent a strong threat to their physical well being, psychological and social. The aim of this study was to identify the main symptoms of Stress Pré-Competitive juvenile Ruffoni Judo of Team. The study was based on a survey of the descriptive type. For the identification of stress symptoms was used a questionnaire called LSSPCI (List of Symptoms of Stress Pre-Competitive Children and Youth). The results showed that 60.7% of students always concern themselves with their opponents before competitions and 46.4% of students always feel excited to participate in the competition, and they cannot wait to compete. Other symptoms also cited, but with a lower incidence, should also be treated with importance. According to the literature and the results obtained, we can consider that the symptoms of pre-competition stress that appear most frequently in the juvenile category are those that provide a high level of anxiety in the moments before the event, and this anxiety can be the result of a charging that the environment and the people involved provide, directly or indirectly. Future research should explore this complex relationship between stress and characteristics of judo practitioners and the various mechanisms that alter these conditions.
Keywords: stress pré-competitive; juvenile; judo